Tiger & Bunny. 8 - Nishida, Masafumi (Viz Media, 2015)
"The heroes have discovered the secret behind the Mad Bears controlled by Kriem and begin to disable the exosuits that are threatening to destroy Stern Bild. Meanwhile, Kotetsu and Barnaby finally figure out what Jake's secret power is!"--Page 4 of cover.